Dying Too Soon: Excess Mortality in Severe Mental Illness - de Mooij, Liselotte D.; Kikkert, Martijn; Theunissen, Jan; Beekman, Aartjan T.F.; de Haan, Lieuwe; Duurkoop, Pim W.R.A.; Van, Henricus L.; Dekker, Jack J.M. (Frontiers in Psychiatry, 2019)
Aims: We aimed to identify baseline predictors of mortality in patients with a severe mental illness (SMI) over a 6-year period and to describe mortality rates as standardised mortality ratios (SMRs). We hypothesised that cardiovascular diseases, older age, cigarette smoking, more severe psychiatric symptoms and more severe psychotropic side effects, and alcohol or drug use were independent risk factors for mortality. Method: Medical examinations were conducted at baseline in a cohort of 322 SMI patients. SMRs were estimated after 6 years and an evaluation was made of the impact of a wide range of variables on survival time. Results: Almost 11% of the SMI patients had died at the end of the study period. All-cause SMRs were 4.51 (95% CI 3.07–5.95) for all SMI patients (4.89, 95% CI 2.97–6.80 for men, and 3.94, 95% CI 1.78–6.10 for women). Natural causes accounted for 86% of excess mortality and unnatural causes for 14%. Cardiovascular disease was a major contributor to this excess mortality. Multivariate Cox regression analyses showed that premature death was associated with a longer history of tobacco use (HR: 1.03, 95% CI 1.02–1.03) and more severe symptoms of disorganisation (HR: 2.36, 95% CI 2.21–2.52). Conclusions: The high SMR and the incidence of cardiovascular disease-related death in SMI patients in our study justify concern. This study underscores the urgent need for interventions to reduce excess mortality in patients with SMI.